Antifouling properties of micro arc oxidation coatings containing Cu2O/ZnO nanoparticles on Ti6Al4V. (January 2016) - Zhao, Dan; Lu, Yuhui; Wang, Zhong; Zeng, Xing; Liu, Shaogang; Wang, Tao
Abstract: Micro arc oxidation (MAO), as a new special surface treatment method, has been introduced to the marine antifouling field for titanium alloys because of the anatase and rutile TiO2 with antibacterial effects obtained during the oxidation process. Despite this, metallic oxide antifouling additives have been added into MAO coatings to improve the antibacterial and antifouling abilities of titanium alloy. In this study, MAO coatings containing nanometer particles were obtained by adding nano Cu2 O and nano ZnO into the electrolyte. Structure, morphology, phase constitution and chemical composition of the MAO coating film were studied by SEM, XRD and EDS. The antibacterial properties of the film were evaluated by exposing the specimens to Escherichia coli and comparing the Ti-MAO and Ti-bared controls. The results showed that the MAO process on Ti6Al4V has an outstanding antibacterial property which can be further enhanced by nano Cu2 O and nano ZnO. The Ti-MAO–Cu2 O group had the best antibacterial ability. These findings indicate that by means of this process adding nanometer metallic oxide into an MAO coating film via an electrolyte is useful for enhancing the antibacterial and antifouling abilities of titanium. Highlights: Micro arc oxidation technology was combined with nanomaterials. Antifouling additives make a better surface morphology. Metallic oxides are effective for antibacterial and antifouling abilities of titanium alloys. Cu2 O nanoparticles have a more obvious antibacterial effect.